The Effect of Good Corporate Governance on Tax Avoidance: An Empirical Study on Manufacturing Companies Listed in IDX period 2010-2013 - Vivi Adeyani Tandean; Winnie (Asian Journal of Accounting Research, 2016)
This study aims to obtain an empirical evidence about the effect of good corporate governance on tax avoidance which becomes a proxy of current ETR (Effective Tax Rate). The samples of this study were 120 manufacturing companies listed in Indonesian Stock Exchange in 2010 – 2013. The hypothesis testing used multiple regression analysis. The result of this study show that audit committee has a positive effect on tax avoidance in partial but the executive compensation, executive character, company size, institutional ownership, boards of commisioners' proportion, audit committee and audit quality have simultaneous effect to define tax avoidance.